0
$\begingroup$

I have this limit to calculate :

$$\lim_{x\rightarrow 0}\frac{x \cos (x) - \sin (x)}{e^{x} - e^{-x} - 2x} $$

I need to know if my solution were true, I explain

  • I use the second order of taylor expansion of $$ \cos(x) = 1 - \frac{x^2}{2} $$
  • I use the first order of taylor expansion of $$ \sin(x) = x $$

    $$ \exp(x) = 1 $$

    $$ \exp(-x) = 1 $$

So I get

$$\lim_{x\rightarrow 0}\frac{x \cos (x) - \sin (x)}{e^{x} - e^{-x} - 2x} = \lim_{x\rightarrow 0}\frac{ \frac{-x^3}{2}}{ - 2x} = 0 $$

$\endgroup$
  • 1
    $\begingroup$ I think the answer is $-1$. $\endgroup$ – Rohan Dec 4 '16 at 15:19
  • 1
    $\begingroup$ the searched limit is equal to $$-1$$ $\endgroup$ – Dr. Sonnhard Graubner Dec 4 '16 at 15:19
  • $\begingroup$ @Rohan how you get this result ? my approach is it false? $\endgroup$ – Lamloumi Afif Dec 4 '16 at 15:20
  • $\begingroup$ I got this limit in an assignment a few months back. Hence, I vaguely remember. Luckily, @Dr.SonnhardGraubner has confirmed it. $\endgroup$ – Rohan Dec 4 '16 at 15:22
2
$\begingroup$

We have

$$x\cos(x)-\sin(x)=x(1-\frac{x^2}{2})-x+\frac{x^3}{6}+x^3\epsilon_1(x)$$

$$=x^3\left(\frac{-1}{3}+\epsilon_1(x)\right).$$

and

$$e^x-e^{-x}-2x=1+x+\frac{x^2}{2}+\frac{x^3}{6}-1+x-\frac{x^2}{2}+\frac{x^3}{6}+x^3\epsilon_2(x)-2x$$

$$=x^3\left(\frac{1}{3}+\epsilon_2(x)\right).$$

thus the limit is $-1$.

$\endgroup$
  • $\begingroup$ I agree with your method, but I need to know exactly what is the error in mine? $\endgroup$ – Lamloumi Afif Dec 4 '16 at 15:40
  • 1
    $\begingroup$ @LamloumiAfif In lines 7,8,9 .you had to expand untill third order. $\endgroup$ – hamam_Abdallah Dec 4 '16 at 15:41
2
$\begingroup$

Your error is that all Taylor's expansions have to be at the same order, otherwise your your results will be meaningless.

  • Numerator: $\; x\cos x=x\Bigl(1-\dfrac{x^2}2+o(x^2)\Bigr)=x-\dfrac{x^3}2+o(x^3)$, hence $$x\cos x-\sin x=x-\dfrac{x^3}2+o(x^3)-\Bigl(x-\dfrac{x^3}6+o(x^3)\Bigr)=-\dfrac{x^3}3+o(x^3)\sim_0-\dfrac{x^3}3$$
    • Denominator: $\;\mathrm e^x-\mathrm e^{-x}-2x=2(\sinh x-x)=2\Bigl(x+\dfrac{x^3}6+o(x^3)-x\Bigr)=\dfrac{x^3}3+o(x^3)\sim_0\dfrac{x^3}3$. Thus the fraction is equivalent near $0$ to $$\frac{-\dfrac{x^3}3}{\phantom{-}\dfrac{x^3}3}=-1.$$
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.